Enzymes Immobilized on Carbon Nitride (C3N4) Cooperating with Metal Nanoparticles for Cascade Catalysis. Issue 6 (28th January 2019) - Wang, Yangxin; Zhang, Ningning; Hübner, René; Tan, Deming; Löffler, Markus; Facsko, Stefan; Zhang, En; Ge, Yan; Qi, Zhenhui; Wu, Changzhu
Abstract: The exploration of effective platforms for immobilizing chemo‐ and biocatalysts to develop biohybrid catalysts is an attractive subject of practical interest. In this work, carbon nitride (C3 N4 ) is used for the first time as a platform for the immobilization of metal catalyst (Pd nanoparticles) and biocatalyst ( Candida antarctica lipase B, CalB) in a facile manner to prepare biohybrid catalyst. The optimal biohybrid catalyst inherits the intrinsic performance of both Pd nanoparticles and CalB, and shows high activity in the one‐pot cascade reaction converting benzaldehyde to benzyl hexanoate at room temperature. With this proof of concept, it is expected that C3 N4 can be utilized for immobilizing more types of chemo‐ and biocatalysts for perspective applications. Abstract : The exploration of new carriers for efficient and durable biohybrid catalysts for cascade reactions is an attractive subject of practical interest. In this work, C3 N4 is utilized as solid support to co‐immobilize Pd nanoparticles and Candida antarctica lipase B for preparing biohybrid catalysts. The catalysts show high catalytic efficiency in a cascade reaction converting benzaldyde to benzyl hexanoate.